Rice flour fermented with Lactobacillus paracasei CBA L74 in the treatment of atopic dermatitis in infants: A randomized, double- blind, placebo- controlled trial. (January 2021) - D'Auria, Enza; Panelli, Simona; Lunardon, Luisa; Pajoro, Massimo; Paradiso, Laura; Beretta, Silvia; Loretelli, Cristian; Tosi, Diego; Perini, Matteo; Bedogni, Giorgio; Abdelsalam, Ahmed; Fiorina, Paolo; et al.
Graphical abstract: Abstract: To assess the effect of a fermented rice-flour obtained from Lactobacillus paracasei CBA L74 in managing infants with moderate to severe atopic dermatitis. Infants with moderate to severe atopic dermatitis, aged 6–36 months, were randomly assigned to receive once-daily consumption of rice flour containing heat-killed probiotic Lactobacillus paracasei CBA L74 or placebo for 12 weeks as supplementary approach to topical treatment. Primary outcome was SCORAD index change from baseline to 12 weeks; secondary outcomes were gut microbiota composition, as evaluated by the analysis of fecal samples, and serum cytokines at baseline and at the end of the intervention period in both groups, and steroid usage over the treatment period and one month after stopping it. V3–V4 region of the 16S ribosomal RNA gene was sequenced to evaluate changes in the gut microbiota. SCORAD index decreased over the treatment period in both groups. The difference in the SCORAD change was -2.1 (-5.5 to 1.3; p = 0.223) for the experimental vs. the placebo group, not reaching the minimal clinical difference of 8.7 units. The use of topical steroids, measured as finger tips units, decreased from 4 to 16 weeks, in both groups; the reduction was significantly higher in experimental than in placebo group (p value from Wilcoxon rank sum test = 0.031). No significant differences were observed for cytokines levels between groups. The composition of gut microbiota at the phylum and class taxonomic levels resulted very similar, at baseline and after intervention, in both groups. Similarly, no significant differences were observed in the relative abundance of bacterial genera between groups. In conclusion, though the heat-killed Lactobacillus paracasei was not proved to be effective in reducing the severity of atopic dermatitis, it showed a steroid sparing effect the value of which needs to be further investigated.